Turning classical states quantum with linear optics and photon counting - Bartley, T; Donati, G; Jin, X; Spring, J; Barbieri, M; Smith, B; Datta, A; Zhang, L; Walmsley, I (2012)
We demonstrate a method to transmute classical light into a quantum state without invoking any nonlinear optical processes. Using a tunable beam splitter and photon number resolving measurement, we create a novel non-Gaussian state. © 2011 Optical Society of America.